Sonic Hedgehog modulates the inflammatory response and improves functional recovery after spinal cord injury in a thoracic contusion-compression model - Zhang, Hao; Younsi, Alexander; Zheng, Guoli; Tail, Mohamed; Harms, Anna-Kathrin; Roth, Judith; Hatami, Maryam; Skutella, Thomas; Unterberg, Andreas; Zweckberger, Klaus (European spine journal, 2021)
Purpose  The Sonic Hedgehog (Shh) pathway has been associated with a protective role after injury to the central nervous system (CNS). We, therefore, investigated the effects of intrathecal Shh-administration in the subacute phase after thoracic spinal cord injury (SCI) on secondary injury processes in rats. - Methods  Twenty-one Wistar rats were subjected to thoracic clip-contusion/compression SCI at T9. Animals were randomized into three treatment groups (Shh, Vehicle, Sham). Seven days after SCI, osmotic pumps were implanted for seven-day continuous intrathecal administration of Shh. Basso, Beattie and Bresnahan (BBB) score, Gridwalk test and bodyweight were weekly assessed. Animals were sacrificed six weeks after SCI and immunohistological analyses were conducted. The results were compared between groups and statistical analysis was performed (p < 0.05 was considered significant). - Results  The intrathecal administration of Shh led to significantly increased polarization of macrophages toward the antiinflammatory M2-phenotype, significantly decreased T-lymphocytic invasion and significantly reduced resident microglia six weeks after the injury. Reactive astrogliosis was also significantly reduced while changes in size of the posttraumatic cyst as well as the overall macrophagic infiltration, although reduced, remained insignificant. Finally, with the administration of Shh, gain of bodyweight (216.6 ± 3.65 g vs. 230.4 ± 5.477 g; p = 0.0111) and BBB score (8.2 ± 0.2 vs. 5.9 ± 0.7 points; p = 0.0365) were significantly improved compared to untreated animals six weeks after SCI as well. - Conclusion  Intrathecal Shh-administration showed neuroprotective effects with attenuated neuroinflammation, reduced astrogliosis and improved functional recovery six weeks after severe contusion/compression SCI.
Gesehen am 07.08.2023